2014
DOI: 10.1111/apt.12815
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: magnetic resonance enterography vs. computed tomography enterography for evaluating disease activity in small bowel Crohn's disease

Abstract: Summary BackgroundMagnetic resonance enterography (MRE) has been proposed as a non-ionising alternative method to computed tomography enterography (CTE). Some studies have directly compared CTE and MRE in patients with small bowel Crohn's disease (CD) with variable results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 37 publications
(69 reference statements)
4
80
0
3
Order By: Relevance
“…However, MRE was superior to CTE in detecting strictures (p = 0.04) and ileal wall enhancement (p = 0.02). A 2014 meta-analysis by Qiu et al [44] of 290 CD patients across six studies, found no significant difference between the diagnostic accuracy of MRE and CTE in detecting active small bowel CD and its complications including fistula, stenosis and abscess formation. Given its proven diagnostic accuracy, updated guidelines by the European Crohn's and Colitis Organisation and the European Society of Gastrointestinal and Abdominal Radiology, advocate increased routine usage of MRI for the assessment of small bowel CD, to reduce radiation exposure in this cohort of patients [45] .…”
Section: Mrementioning
confidence: 99%
“…However, MRE was superior to CTE in detecting strictures (p = 0.04) and ileal wall enhancement (p = 0.02). A 2014 meta-analysis by Qiu et al [44] of 290 CD patients across six studies, found no significant difference between the diagnostic accuracy of MRE and CTE in detecting active small bowel CD and its complications including fistula, stenosis and abscess formation. Given its proven diagnostic accuracy, updated guidelines by the European Crohn's and Colitis Organisation and the European Society of Gastrointestinal and Abdominal Radiology, advocate increased routine usage of MRI for the assessment of small bowel CD, to reduce radiation exposure in this cohort of patients [45] .…”
Section: Mrementioning
confidence: 99%
“…The exposure to ionizing radiation with CTE, however, constrains its application for the repeated assessment of disease activity and MH. 65,66 Initial studies investigating the value of MRE in monitoring disease activity and treatment response showed inconsistent results. Some investigators demonstrated a significant correlation between MRE signal intensity and treatment response, 67 whereas others found that, although significant improvements in MRE findings occurred, normalization of findings with treatment was rare despite meaningful changes in clinical disease activity.…”
Section: Magnetic Resonance Enterographymentioning
confidence: 99%
“…70 Given the enhanced sensitivity over other small-bowel imaging techniques (Table 4), 65,71,72 consideration has been given to using VCE as the first or second line diagnostic test for the assessment of MH. An initial prospective study of 40 patients with known or suspected nonstricturing, nonpenetrating CD investigated the use of VCE for assessment of MH during an acute CD flare.…”
Section: Video Capsule Endoscopymentioning
confidence: 99%
“…In addition to endoscopy, ultrasonography, CT and MRI are widely used for evaluation of gut inflammation in IBD [11,12,28,29] . These 3 techniques have a high comparable diagnostic accuracy for the detection of lesions in IBD.…”
Section: Introductionmentioning
confidence: 99%